The integral role of the Black Soldier fly, Hermetia illucens L., microbiota in its life history - Ment, Dana; Mishra, Sapna (Frontiers in Microbiomes, 2025)
The Black Soldier fly (BSF), Hermetia illucens, exhibits versatile bioconversion abilities and effectively transforms various waste materials into a nutritious biomass suitable for consumption. The degradation ability of BSF larvae has been attributed to their gut microbiota. Therefore, this review explores the role of the BSF microbiota throughout the BSF life stages in the bioconversion, focusing on the BSF larvae and its microbiota. We reflect on the microbiota’s contribution to life cycle aspects, growth, reproduction, immune response, and waste breakdown. The key points discussed include the gut microbiota in organic waste bioconversion by BSF larvae, the role of microbiota in BSF oviposition and growth throughout its life history, and microbiota’s role in immunity with a specific focus on antimicrobial peptides. Where knowledge gaps were identified for BSF, we provide examples of closely related dipteran insects or insects with well-studied microbiota functioning. The significant role of the BSF gut microbiota is enabling its versatile waste degradation while conferring protection against pathogens and xenobiotic compounds. As such, we discuss the future perspectives that microbiome engineering may offer for BSF.